Liver hyperplasia after tamoxifen induction of Myc in a transgenic medaka model - Luciana A. Menescal; Cornelia Schmidt; Daniel Liedtke; Manfred Schartl (The Company of Biologists, 2012)
SUMMARY Myc is a global transcriptional regulator and one of the most frequently overexpressed oncoproteins in human tumors. It is well established that activation of Myc leads to enhanced cell proliferation but can also lead to increased apoptosis. The use of animal models expressing deregulated levels of Myc has helped to both elucidate its function in normal cells and give insight into how Myc initiates and maintains tumorigenesis. Analyses of the medaka (Oryzias latipes) genome uncovered the unexpected presence of two Myc gene copies in this teleost species. Comparison of these Myc versions to other vertebrate species revealed that one gene, myc17, differs by the loss of some conserved regulatory protein motifs present in all other known Myc genes. To investigate how such differences might affect the basic biological functions of Myc, we generated a tamoxifen-inducible in vivo model utilizing a natural, fish-specific Myc gene. Using this model we show that, when activated, Myc17 leads to increased proliferation and to apoptosis in a dose-dependent manner, similar to human Myc. We have also shown that long-term Myc17 activation triggers liver hyperplasia in adult fish, allowing this newly established transgenic medaka model to be used to study the transition from hyperplasia to liver cancer and to identify Myc-induced tumorigenesis modifiers.